Comparison of health technology assessment for new medicines in France and England: an example based on ixazomib for patients with relapsed or refractory multiple myeloma. Issue 1 (1st January 2019) - Armoiry, Xavier; Spath, Hans-Martin; Clarke, Aileen; Connock, Martin; Sutcliffe, Paul; Dussart, Claude
ABSTRACT: Introduction : The appraisal of medicines is often a complex and iterative process. We compared the health technology assessment (HTA) process in England and France taking as a case study the example of ixazomib for multiple myeloma. Methods : We undertook an analysis of eight relevant published documents identifed from the websites of the French and English HTA bodies (HAS and NICE, respectively). We analyse patients' availability of ixazomib resulting in the different stages of the appraisal process. Results : We identified differences in the assessment, one of these being the use of an appraisal scope in England allowing the differentiation of populations and comparators according to previously approved treatments. Ixazomib became available earlier in France as part of an early access programme, but the availability was soon discontinued for newly eligible patients following an HAS determination that Ixazomib yielded no additional benefit. This opinion resulted in long pricing discussions. In England, despite the absence of an early access programme and following a process that included cost-effectiveness evaluation combined with pricing discussions, the medicine was fairly rapidly recommended for use. Conclusions : Differences in the HTA process may result in appreciable differences in time from marketing authorisation to health service adoption of newly licensed drugs.